CULTURAL VALUE IN PARUNTUK KANA FOR THE SOCIETY: A ROLAND BARTHES SEMIOTICS - Indah, Nur; Rapi, Muhammad; Nensilianti, Nensilianti (Media Inovasi Pendidikan dan Publikasi, 2025)
This study aims to examine the symbolic meaning and cultural values contained in Paruntuk Kana in the life of the Jeneponto community from the perspective of Roland Barthes' semiotics. The method used is descriptive qualitative research, with primary data sourced from the classic literary document Pasang dan Paruntuk Kana by Zainuddin Hakim and verified through interviews and field observation. The findings indicate that Paruntuk Kana functions as a functional symbolic sign system. Semiotically, the expressions operate through two layers: denotative, as the concrete, literal meaning, and connotative, as the layer where cultural values are embedded, serving as social control. The cultural values found within Paruntuk Kana collectively form an essential communal ethical guide, including: the value of honesty (lambusuk) which is the principal capital for integrity; the value of leadership which condemns opportunistic behavior and demands responsibility; the value of unity which emphasizes cohesion based on truth and justice; and the value of sirik (shame/dignity) which is the highest sense of honor and acts as the strongest mechanism for social control. This research contributes to understanding Paruntuk Kana's role as an essential cultural identity in maintaining the ethical behavior and social stability of the Jeneponto community.